Hubungan Mutu Pelayanan Hemodialisis dengan Tingkat Kepuasan Pasien di Instalasi Hemodialisis Rumah Sakit Tingkat III Kota Jambi - Dianita Indriani; Dwi Noerjoedianto; Willia Novita Eka Rini; Ummi Kalsum; Asparian Asparian; Fairuz Quzwain (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2026)
Chronic kidney disease (CKD) is one of the main contributors to the highest mortality and suffering rates in the 21st century. Based on global data in 2022, chronic kidney disease (CKD) affects more than 10% of the world's population, with an estimated 843 million people affected. Research results from the 2023 Indonesian Health Survey (SKI) data, the prevalence of chronic kidney failure (CKD) in Indonesia is 0.22% of the total population, an estimated 638,178 people suffer from CKD throughout Indonesia. Jambi Province has 0.15% of the population suffering from chronic kidney failure. Based on data on hemodialysis patient visits at Dr. Bratanata Class III Hospital, there is an increase in the number of visits from year to year. This study aims to analyze the relationship between the quality of hemodialysis services and patient satisfaction levels in the Hemodialysis Installation of Dr. Bratanata Class III Hospital. A total sampling technique was used to conduct the study in 2026, involving 86 patients with chronic kidney disease (CKD) undergoing hemodialysis treatment at the outpatient hemodialysis unit. Data were analyzed using the chi-square test and logistic regression. The study found a relationship between the dimensions of "Tengibels," "Reliability," "Responsiveness," and "Empathy" with patient satisfaction at the Hemodialysis Unit III of Dr. Bratanata Jambi Hospital, with p-values ​​of 0.004, 0.012, 0.008, and 0.001, respectively. The most dominant factor associated with patient satisfaction at the Hemodialysis Unit III of Dr. Bratanata Jambi Hospital was the "Empathy" dimension (P-value = 0.108). Hospital management is expected to continuously improve service quality across all aspects of the "Tenibels," "Reliability," "Responsiveness," "Assurance," and "Empathy" dimensions.